Turning out for redistribution: the effect of voter turnout on top marginal tax rates - Navid Sabet (Public Choice, 2023)
I investigate the impact of voter turnout on top marginal tax rates in OECD countries between 1974 and 2013. I find that higher turnout leads to higher taxes for top earners, a result broadly consistent with the median voter theorem. Using novel survey data, I confirm that individuals in all but the wealthiest income bracket prefer higher taxes on the rich more than they prefer greater government spending in the economy. In line with these preferences, I find that turnout has a significantly negative effect on top income shares but no effect on the size of government or on public welfare expenditure. An instrumental variables approach confirms my findings. Overall, the paper is the first of its kind to link turnout to measures of redistribution that affect top earners and to preferences for redistribution.
Keywords: H24; D31; D7; 330; Voter turnout; Preferences for redistribution; Elections; Top tax rates